A brief study on the economic and technical feasibility of a small biomass power plant - the case of Morretes, Paraná, Brazil. (2016) - Zuba, MÁrcio Eduardo; Catapan, Anderson; Souza, Marília De; Silva, Marcus Vinicius GonÁalves Da
Brazil is one of the biggest agricultural producers in the world, and the uncontested leader in sugarcane production. One main by-product of sugarcane is bagasse which has a high energy potential and is used as fuel in large thermal power generation stations located within sugar and ethanol plants. However, this is not the reality of small sugarcane producers, which use just a fraction of bagasse as animal feed, improperly discarding outdoors all the rest, thus causing many environmental problems. The objective of this paper is, from a case study conducted in a small town in Paraná (Southern Brazil), to check the technical and financial feasibility of implementing local-level small-scale thermal power generation stations, which could use the surplus sugarcane biomass. The conclusion not only indicates it is feasible, but also that there are benefits that go beyond the financial sphere, regarding the environment and the national energy deficit.